PPARδ Attenuates Alcohol-Mediated Insulin Resistance by Enhancing Fatty Acid-Induced Mitochondrial Uncoupling and Antioxidant Defense in Skeletal Muscle - Koh, Jin-Ho; Kim, Ki-Hoon; Park, Sol-Yi; Kim, Yong-Woon; Kim, Jong-Yeon (Frontiers in Physiology, 2020)
Alcohol consumption leads to the dysfunction of multiple organs including liver, heart, and skeletal muscle. Alcohol effects on insulin resistance in liver are well evidenced, whereas its effects in skeletal muscle remain controversial. Emerging evidence indicates that alcohol promotes adipose tissue dysfunction, which may induce organ dysregulation. We show that consumption of ethanol (EtOH) reduces the activation of 5′AMP-activated protein kinase (AMPK) and mammalian target of rapamycin (mTOR) as well as the protein of carnitine palmitoyltransferase 1 (CPT1) and glucose transporter type 4 (GLUT4) in C2C12 myotube. We observed that chronic EtOH consumption increases free fatty acid levels in plasma and triglyceride (TG) accumulation in skeletal muscle and that these increases induce insulin resistance and decrease glucose uptake. Hence, ethanol dysregulates metabolic factors and induces TG accumulation. We found peroxisome proliferator-activated receptor β/δ (PPARδ) activation recovers AMPK activation and increases carnitine-acylcarnitine translocase (CACT) protein. These effects may contribute to enhance mitochondrial activation via uncoupling protein 3 (UCP3) when fatty acids are used as a substrate, thus reduces EtOH-induced increases in TG levels in skeletal muscle. In addition, PPARδ activation recovered EtOH-induced loss of protein kinase B (AKT) phosphorylation at serine 473 via rapamycin-insensitive companion of mammalian target of rapamycin (Rictor) activation. Importantly, PPARδ activation enhanced mitochondrial uncoupling via UCP3. Taken together, the study shows PPARδ enhances fatty acid utilization and uncoupled respiration via UCP3 and protects against EtOH-induced lipotoxicity and insulin resistance in skeletal muscle.